Condition Monitoring System of a Three Phase Induction Motor Against Thermal Overloading - Bhattacharjee, Parthabrata; Roy, Amartya (International Journal of Computer Sciences and Engineering, 2025)
Cooling fan is used primarily to dissipate heat. All types of equipment with mechanical operations, regardless of industry sector, generate heat. For many machines, excess heat that is not rapidly and effectively dissipated can cause a shortened lifespan and even mechanical failure. Heat is capable of damaging a machine, sometimes irreversibly. The use of a cooling fan, therefore, is crucial for protecting the optimal functioning and the life of machinery. For this reason, cooling solutions like fans or blowers are widely used to enable equipment and machines to perform reliably. Cooling fans disperse hot air from within a machine and bring in cooler air from the outside so that the machine can work in optimal conditions. Some types of equipment use more than one fan to maintain a constant temperature. So in our project we are proposing a protective scheme for industrial motor from the phenomenon called thermal overloading